The category of definiteness and its investigation in Lithuanian linguistics - Spraunienė, Birutė (Lietuvių kalba, 2008)
The paper analyses the concept of definiteness and the semantics and formal expression of the category of definiteness. It also offers an overview of the concept of the category and its investigation in Lithuanian linguistics. Definiteness helps solve problems of the referent identification in the course of communication and is a universal semantic/pragmatic category. In languages with a grammatical expression of definiteness and formally marked by articles, the category of definiteness is grammatical. Articles mainly serve as a means of coordinating reference; however, eventually their usage might become wider and the number of functions might increase. As a result, they gradually seep into indefinite contexts. Since languages manifest a varied expression of definiteness, in contrastive studies only the semantic content of the category can serve as a tertium comparationis. It can be broadly defined in the following way: the semantics of definite description is characterised by its referent which is known to the addressee or can be easily and unambiguously identified and is the only one (unique and maximum) in a certain pragmatic set. The semantics of indefinite description is characterised by an addressee who/which is unable to identify the referent and in respect to uniqueness such description is neutral. The expression of definiteness in Lithuanian can hardly be treated as grammatical, with the pronominal morpheme of the definite form of adjectives being the only formal marker of definiteness. Previous research has been fairly scarce in identifying the contrast, distribution and functions of definite and indefinite forms in Lithuanian. For example, there has been no research done when the definite form is obligatory, when it is optional or when its usage is ungrammatical. Definiteness in Lithuanian is also expressed by demonstrative pronouns; and some of them, according to Albertas Rosinas, have become dysfunctional and presently perform the function of definite markers in spoken language. Definiteness also correlates with the functional sentence perspective and word order as well as the opposition between the nominative /accusative vs the genitive case. However, in Lithuanian to finally discriminate between the definite and the indefinite interpretation is only possible by referring to context.
Keywords: none